Effect of specific strength and power training on serving velocity in tennis players - Williams, J. A. (Journal of Australian Strength and Conditioning, 2020)
Professional Tennis players are amongst some of the fittest and most robust individuals in the modern sporting world. Greater attention is gradually being placed on Strength and Conditioning (S&C) training for the modern-day Tennis athlete, as significant forces and torques are generated through performing their respective strokes, most notably the Serve. The purpose of this paper was to outline the contribution of the lower- and upper-body on the serving motion, and their impact on absolute ball velocity. A thorough search for literature was conducted via Google Scholar. 25 primary articles was narrowed down to 11 based off inclusion criteria that consisted of a) Tennis experience, b) training program focus, and c) serving velocity measurement. Two of the 11 studies failed to show any positive change in serving velocity which may result from methodological considerations. Majority of studies demonstrated improvements in serving velocity, ranging from ~3.0-29.0%. This large margin reflects the studies differing timeframes, spanning between 4-weeks and 9-months. Majority of the contribution for absolute ball speed comes predominately from lower-body and trunk regions (~50% of total kinetic chain force). The shoulders prove to have a significant contribution to the pace of the ball, however injuries are most common in this region due to agonist-antagonist imbalances. Trunk musculature provides great dynamic support during the momentum shifting of the serving motion. The Tennis serve is fundamentally a whole-body explosive kinetic-chain movement that requires significant practice, especially surrounding technique and coordination. Adopting a full-body periodised S&C program is best suited for the modern-day athlete, with the integration of lower- and upper-body plyometric exercises, and trunk strength and stability.